The Impact of Increased PEEP on Hemodynamics, Respiratory Mechanics, and Oxygenation in Pediatric ARDS - Junqueira, Fernanda M. D. (2024)
BACKGROUND: PEEP is a cornerstone treatment for children with pediatric ARDS. Unfortunately, its titration is often performed solely by evaluating oxygen saturation, which can lead to inadequate PEEP level settings and consequent adverse effects. This study aimed to assess the impact of increasing PEEP on hemodynamics, respiratory system mechanics, and oxygenation in children with ARDS. METHODS: Children receiving mechanical ventilation and on pressure-controlled volume-guaranteed mode were prospectively assessed for inclusion. PEEP was sequentially changed to 5, 12, 10, 8 cm H2O, and again to 5 cm H2O. After 10 min at each PEEP level, hemodynamic, ventilatory, and oxygenation variables were collected. RESULTS: A total of 31 subjects were included, with median age and weight of 6 months and 6.3 kg, respectively. The main reasons for pediatric ICU admission were respiratory failure caused by acute viral bronchiolitis (45%) and communityacquired pneumonia (32%). Most subjects had mild or moderate ARDS (45% and 42%, respectively), with a median (interquartile range) oxygenation index of 8.4 (5.8–12.7). Oxygen saturation improved significantly when PEEP was increased. However, although no significant changes in blood pressure were observed, the median cardiac index at PEEP of 12 cm H2O was significantly lower than that observed at any other PEEP level (P 5.001). Fourteen participants (45%) experienced a reduction in cardiac index of > 10% when PEEP was increased to 12 cm H2O. Also, the estimated oxygen delivery was significantly lower, at 12 cm H2O PEEP. Finally, respiratory system compliance significantly reduced when PEEP was increased. At a PEEP of 12 cm H2O, static compliance had a median reduction of 25% in relation to the initial assessment (PEEP of 5 cm H2O). CONCLUSIONS: Although it may improve arterial oxygen saturation, inappropriately high PEEP levels may reduce cardiac output, oxygen delivery, and respiratory system compliance in pediatric subjects with ARDS with low potential for lung recruitability.